The spinal nerves that constitute the plexus lumbosacrales of the red squirrel (Sciurus vulgaris) - Aydin, A. (Czech Academy Agricultural Sciences, 2010)
This study was aimed at investigating the lumbosacral plexus of squirrels (Sciurus vulgaris). Ten squirrels were used in this work. The animals were carefully dissected and the spinal nerves that constitute the lumbosacral plexus were examined. It was discovered that the lumbosacral plexus was formed by L6, L7, S1, S2 in nine animals and in the one remaining animal in addition to these branches rami ventralis of L4 and L5 were forming the plexus. The common root forming the last part of the lumbosacral plexus and giving branches dispersing to the hind limb was formed by the rami ventralis of L6, L7, S1, S2. Thus, in squirrels, the spinal nerves forming the lumbosacral plexus and the joining of these spinal nerves to each other differs from other rodents and mammals.
Keywords: lumbosacral plexus; nerves; the red squirrel (Sciurus vulgaris)